(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The aim of the present study was to find outthe problems of itinerant teacher working under SSA. The preceding chapterincluded the detailed description about the methodology of the present study.In this chapter the data collected were analyzed with suitable interpretationin relation to the objectives. The data has been presented in the form oftables and figures wherever necessary.